2014
DOI: 10.1155/2014/527918
|View full text |Cite
|
Sign up to set email alerts
|

rs744166 Polymorphism of theSTAT3Gene Is Associated with Risk of Gastric Cancer in a Chinese Population

Abstract: The aim of this study was to explore the association between polymorphisms in signal transducer and activator of transcription protein 3 (STAT3) and the risk of gastric cancer. In the present study, a case-control study was conducted in which rs2293152 and rs744166 polymorphisms in STAT3 were analyzed in 209 Chinese patients with gastric cancer and 294 cancer-free controls. The genotypes were determined by polymerase chain reaction restriction fragment length polymorphism method. For the rs744166 polymorphism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…It is known that the C allele of rs744166 leads to a higher basal expression level of STAT3. 24) In this study, we clarified that patients with CC genotypes at STAT3 rs744166 had a significantly lower incidence of stomatitis compared with those with TT+TC. In recent works, sunitinib was reported to induce RCC cell apoptosis and to decrease immunosuppressive cell numbers as a result of STAT3 inhibition.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It is known that the C allele of rs744166 leads to a higher basal expression level of STAT3. 24) In this study, we clarified that patients with CC genotypes at STAT3 rs744166 had a significantly lower incidence of stomatitis compared with those with TT+TC. In recent works, sunitinib was reported to induce RCC cell apoptosis and to decrease immunosuppressive cell numbers as a result of STAT3 inhibition.…”
Section: Discussionmentioning
confidence: 74%
“…In recent works, sunitinib was reported to induce RCC cell apoptosis and to decrease immunosuppressive cell numbers as a result of STAT3 inhibition. 1,[24][25][26][27] STAT3 is activated by the stimulation of IL-6 and growth factors, and is then involved in the regulation of cellular differentiation, survival, and proliferation. 28,29) Immune systems such as Toll-like receptor signaling and B-cell receptor signaling and inflammatory cytokines relate to stomatitis development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we removed 3 studies because their genotype distributions among the controls deviated from HWE (Domańska et al 2013;Xu 2013;Zhang 2011). Therefore, a total of 16 case-control studies from 15 articles (Butterbach et al 2011;Chen et al 2013;Huang et al 2014;Jiang et al 2011;Kwon et al 2011;Liu et al 2014;Slattery et al 2013;Vaclavicek et al 2007;Wang et al 2011Wang et al , 2013Xie et al 2012aXie et al , 2013Yuan et al 2014;Zhao et al 2015) were selected. Of those, there were 5 studies (Jiang et al 2011;Liu et al 2014;Vaclavicek et al 2007;Xie et al 2013;Yuan et al 2014) with 2177 cases and 2484 controls concerning rs2293152 polymorphism, 7 studies Jiang et al 2011;Wang et al 2011Wang et al , 2013Xie et al 2013;Zhao et al 2015) with 3879 cases and 3486 controls concerning rs4796793 polymorphism, 5 studies (Butterbach et al 2011;Chen et al 2013;Jiang et al 2011;Kwon et al 2011) with 3471 cases and 4527 controls concerning rs12949918 polymorphism, 4 studies (Butterbach et al 2011;Chen et al 2013;Slattery et al 2013;Xie et al 2012a) with 3466 cases and 3963 controls concerning rs6503695 polymorphism and 3 studies (Jiang et al 2011;Xie et al 2012a;Yuan et al 2014) with 854 cases and 1045 controls concerning rs744166 po...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The STAT3 gene is located on chromosome 17q21. Several studies have investigated the association between single-nucleotide polymorphisms (SNPs) in the STAT3 gene and cancer risk in diverse populations (Butterbach et al 2011;Chen et al 2013;Domańska et al 2013;Huang et al 2014;Jiang et al 2011;Kwon et al 2011;Liu et al 2014;Slattery et al 2013;Vaclavicek et al 2007;Wang et al 2011Wang et al , 2013Xie 2012b;Xie et al 2012aXie et al , 2013Xu 2013;Yang 2013;Yuan et al 2014;Zhang 2011Zhao et al 2015;Zhong et al 2012). Of those SNPs, five were most commonly studied ones: rs2293152 (in intron 11), rs4796793 (in the promoter), rs12949918 (in intron), rs6503695 (in intron 2), and rs744166 (in intron 1).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies indicated that STAT3 can be activated by the X protein of HBV and activated STAT3 can also bind with the HBV enhancer 1 to activate gene expression, suggesting the interplay between STAT3 and X protein in promoting HCC development (Waris and Siddiqui, 2002). In addition to the functions of STAT3 and HBV infection, several lines of evidence have indicated that single nucleotide polymorphisms (SNPs) in STAT3 gene are associated with susceptibility to malignant development or response to therapy in several types of cancer such as cervical, gastric and renal cancers (Wang et al, 2011;Eto et al, 2013;Yuan et al, 2014). Along with the above-mentioned evidences, it would be interested that the SNPs in STAT3 gene may potentially contribute to the susceptibility of HCC.…”
Section: Association Of Single Nucleotide Polymorphism Rs1053004 Inmentioning
confidence: 99%